The Impact Of Stunting Prevention Counseling Through Education On The Importance Of The First 1,000 Days Of Life - Riza Savita Riza Savita; Nadya Nuraini Putri; Dea Amanda Budi Lestari; Natasya Ayu (International Journal of Health Engineering and Technology, 2026)
Stunting remains a public health issue in Indonesia, including Tanjung Gunung Village, Central Bangka Regency. Limited maternal knowledge of nutrition during the first 1,000 days of life (1,000 HPK), suboptimal breastfeeding practices, and cultural food taboos contribute to stunting risk. This community service aims to improve nutritional knowledge among high-risk pregnant women (4T) as a stunting prevention effort. A descriptive design with a participatory educational approach was applied through interactive counseling and discussion. The activity involved 25 high-risk pregnant women using leaflets and audiovisual media. Evaluation was conducted descriptively through observation of participation and responses. The results showed good acceptance of the material and high participant engagement. Community-based 1,000 HPK nutrition education is feasible as a promotive and preventive strategy for stunting prevention.